Post-collisional shortening in the late Pan-African Hamisana high strain zone, SE Egypt: field and magnetic fabric evidence - Wall, Helga de; Greiling, Reinhard O.; Sadek, Mohamed F. (Precambrian research, 2001)
The Hamisana zone (HZ) is one of the major high strain zones of the Pan-African (Neoproterozoic) Arabian-Nubian shield (ANS). It trends broadly N-S from northern Sudan into southeastern Egypt and meets the present Red Sea coast at ≈23°N. The HZ has been the subject of controversy with regard to its importance for the Pan-African structural evolution. Interpretations range from a suture zone, a regional shear zone, or a large-scale transpressional wrench fault system. In this study, we characterize the nature of the high strain deformation by applying the anisotropy of magnetic susceptibility method along with field and microstructural investigations. These investigations demonstrate that deformation in the HZ is dominated by pure shear under upper greenschist/amphibolite grade metamorphic conditions, producing E-W shortening, but with a strong N-S-extensional component. This deformation also led to folding of regional-scale thrusts (including the base of ophiolite nappes such as Gabal Gerf and Onib). Consequently, the high strain deformation is younger than ophiolite emplacement and suturing of terranes. A weak subsequent overprint was mostly non-coaxial. It took place under considerably lower temperature and led to a minor NE-SW-trending, dextral wrench fault. Although it is of only local importance this fault may be itself a conjugate relative to the prominent NW-SE-trending sinistral Najd faults in the northern ANS. Therefore, the HZ is dominated by late orogenic compressional deformation and cannot be related to either large-scale transpressional orogeny or major escape tectonics.